Frequency of scapular dyskinesis and its relationship with disease parameters in patients with ankylosing spondylitis: a cross-sectional study - Sertaç Ketenci; Bora Uzuner; Dilek Durmuş; Deniz Şahinkaya; Muharrem Yüksel; Ahmet Kıvanç Cengiz (São Paulo Medical Journal)
ABSTRACT BACKGROUND Scapular dyskinesis (SD) is a condition associated with impaired scapular movement caused by cervical, shoulder, and postural abnormalities. OBJECTIVE: The aim of this study was to determine the frequency of SD in patients with ankylosing spondylitis (AS). DESIGN AND SETTING: A cross-sectional study was conducted at Ondokuz Mayıs University, Samsun, Turkey. METHODS: One hundred patients with AS but without shoulder involvement (74 males and 26 females) and 50 healthy controls (35 males and 15 females) were included in the study. The patients were divided into two groups: patients with and without SD. SD was assessed using the Scapular Dyskinesis Test and Lateral Scapular Slide Test. Disease activity, spinal mobility, and chest expansion were also measured. The severity of enthesitis was evaluated using the Spondyloarthritis Research Consortium of Canada index. RESULTS: There were significant differences between the two groups of patients with AS, those with SD, and those without SD in terms of age, chest expansion, and the Bath Ankylosing Spondylitis Metrology Index (BASMI) scores (P < 0.05). The groups differed significantly in terms of hip, thoracic, and lumbar involvement (P < 0.05). The BASMI score was a significant variable affecting SD (P < 0.05). No cases of SD were observed in the control group. CONCLUSION: While there were no significant differences in disease activity and enthesitis scores between patients with and without SD, differences were detected in mobility parameters. Since shoulder examinations of the patients were normal, it can be inferred that SD occurred because of the involvement of the scapulothoracic joints and thoracic spine.